Sarcoidosis and autoimmunity: In the depth of a complex relationship - Rizzi, Luigi; Sabbà, Carlo; Suppressa, Patrizia (Frontiers in Medicine, 2022)
Sarcoidosis is a chronic granulomatous disease that can virtually affect any organ. Its etiology is unknown, although it has been proposed that environmental or biological agents can act as triggers, ultimately leading to chronic inflammation in genetically predisposed individuals. The main component of sarcoid inflammation is represented by an exaggerated T- lymphocytic cellular response to a putative antigen that could not be efficiently cleared in the patient. However, several clinical and immunological observations, such as the association of sarcoidosis to autoimmune diseases or the presence of autoantibodies in the serum of patients with sarcoidosis, suggest that humoral-mediated immune response might also play a role in the pathogenesis of sarcoidosis. The aim of this review is to deepen the relationship between sarcoidosis and autoimmunity, by analyzing the most recent advances and proposing new fields of research.